Combining pieces: a thorough analysis of light activation boosting power and co-substrate preferences for the catalytic efficiency of lytic polysaccharide monooxygenase MtLPMO9A - Ana Gabriela Sepulchro (Green Wave Publishing of Canada, 2021)
Cost-efficient plant biomass conversion using biochemical and/or chemical routes is essential for transitioning to sustainable chemical technologies and renewable biofuels. Lytic polysaccharide monooxygenases (LPMOs) are copper-dependent enzymes that make part of modern hydrolytic cocktails destined for plant biomass degradation. Here, we characterized MtLPMO9A from Thermothelomyces thermophilus M77 (formerly Myceliophthora thermophila) and demonstrated that it could be efficiently driven by chlorophyllin excited by light in the presence of a reductant agent. However, in the absence of chemical reductant, chlorophyllin and light alone do not lead to a significant release of the reaction products by the LPMO, indicating a low capacity of MtLPMO9A reduction (either via direct electron transfer or via superoxide ion, O2•-). We showed that photocatalysis could significantly increase the LPMO activity against highly crystalline and recalcitrant cellulosic substrates, which are poorly degraded in the absence of chlorophyllin and light. We also evaluated the use of co-substrates by MtLPMO9A, revealing that the enzyme can use both hydrogen peroxide (H2O2) and molecular oxygen (O2) as co-substrates for cellulose catalytic oxidation.